A comparative study on the various combination of trichoderma-composted Ipil-ipil (Leucaena Leucocephala, Lam.) and Sugarcaen Bagasse. - Demogena, Glenda A. (1997.)
Bagasse, the end product remaining after the extraction of pure brown sugar, presents a problem in handling and utilization because of its bulk. Being an end-product of biological origin, bagasse could be used as substrate for Trichoderma-composting. Compost recovered however, gives a low fertility level and is beneficial only by improving soil's physical structure. With the use of ipil-ipil, a nitrogen rich substrate, this study aimed (1) To compare the composting time of the various combinations using the following indices: homogeneity, color, odor, and temperature and (2) to compare the NPK content of the various combinations., The experiment was carried out in three ratios of ipil-ipil to bagasse set-up A - 1.5, set-up B-3.5, and set-up C-5:5. Composting procedure in this study were adapted from Cuevas (1988). The data gathered include temperature, pH, and NPK content of the compost. Data gathered were statistically analyzed using the one-way Analysis of Variance (ANOVA) and significant results were further analyzed using the Duncan's Multiple Range Test (DMRT).(p)Set-up C was the first to reach the maturity period at day 40 followed by set-up B (52 days) then set-up A (60) days). Sept-up B however, gave a significantly higher nitrogen and potassium oxide content compared to other combinations (p<0.05). Overall results of this study show that Leucaena leucocephala is a good substrate additive for accelerating maturity and increasing the NPK content. A 3:5 ratio of ipil-ipil to bagasse however, is recommended for composting.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Ipil-ipil -- Research; Leucaena Leucocephala -- Research